P.S.1 / MoMA : Strangers/Étrangers. - Heiss, Alanna; Pietroiusti, Cesare; Herkenhoff, Paulo; Lowry, Glenn D; P.S.1 Contemporary Art Center, New York (New York : P.S.1 Contemporary Art Center, 2001)
Yamaide, Jun'ya ; Jeane, Norma ; ten Gate, Ritsaert ; Philipsz, Susan ; Giles, Thomas ; Abdessemed, Adel ; Healy, Martin ; Munoz, Begona ; Seok, Yoon Young ; Middendorf, Angelika ; Büchel, Christopher ; et al.
Strangers/Étrangers, 2000-2001 P.S.1 National and International Studio Exhibition, 04/26 - 06/09/2001, P.S.1 Contemporary Art Center, New York
kunstcatalogus